2022
DOI: 10.3390/ijerph191911980
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences of Sarcopenia in an Elderly Asian Population: The Prevalence and Risk Factors

Abstract: The loss of muscle mass is widespread in age-related health phenomena in the elderly population. This study examined the prevalence of sarcopenia in a community-dwelling elderly population according to gender. The study also identified gender-specific risk factors in older people aged 75–84 years old. One thousand two hundred and ninety-three participants aged between 75 and 84 years from the National Health and Nutrition Examination Surveys in Korea were investigated. The prevalence of sarcopenia in males and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
33
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 63 publications
1
33
0
Order By: Relevance
“…In the present study, we discovered that PSA group participants were more likely to be women than their non‐PSA counterparts. The result is consistent with previous research emphasizing sex differences in sarcopenia, and showing that women were more frequently influenced by sarcopenia than men 26–28 . We noted that the majority of PSA group members had shorter sleep duration and lower bodyweight.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the present study, we discovered that PSA group participants were more likely to be women than their non‐PSA counterparts. The result is consistent with previous research emphasizing sex differences in sarcopenia, and showing that women were more frequently influenced by sarcopenia than men 26–28 . We noted that the majority of PSA group members had shorter sleep duration and lower bodyweight.…”
Section: Discussionsupporting
confidence: 93%
“…The result is consistent with previous research emphasizing sex differences in sarcopenia, and showing that women were more frequently influenced by sarcopenia than men. [26][27][28] We noted that the majority of PSA group members had shorter sleep duration and lower bodyweight. The present results are in line with that of a prospective study.…”
Section: Discussionmentioning
confidence: 80%
“…This corresponds to findings from studies by Yuenyongchaiwat et al 38 and Chew et al 66 Another study by Du et al 67 conducted among 631 subjects supported this statement by stating that levels of testosterone and insulin‐like growth factor‐1 levels decreased significantly in older males, which caused rapid loss of muscle mass and strength compared to their female counterparts. However, Wang et al 56 and Samper‐Ternent et al 49 from the current study reported otherwise, stating that the prevalence of sarcopenia among females was higher than in males, and there were also other studies supporting this outcome 68,69 . Older women experience menopause, which causes hormonal changes.…”
Section: Discussionmentioning
confidence: 51%
“…At the same time, women also experience a higher rate of diminishing sex hormones like oestrogens and androgens than men. 69,70 The gender differences in sarcopenic prevalence were also demonstrated in a systematic review and meta-analysis of 109 studies involving community-dwelling older adults across several different sarcopenia categories. The consensus reported that gender has a greater role in sarcopenia, and the used to diagnose sarcopenia and the regions subjects are from have a great influence.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation